1985
DOI: 10.1149/1.2113741
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conduction in Agl ‐ Al2 O 3 Composites

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…16 the electrical conductivity of the ␣-Bi 2 O 3 phase has been also plotted, it is about three orders of magnitude smaller than the nanocomposite one. A possible explanation of these observations is a composite effect 37,38 : the internal stresses induced by the Bi rich minority phase increase the concentration and the mobility of the points defects responsible for the ionic conductivity.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…16 the electrical conductivity of the ␣-Bi 2 O 3 phase has been also plotted, it is about three orders of magnitude smaller than the nanocomposite one. A possible explanation of these observations is a composite effect 37,38 : the internal stresses induced by the Bi rich minority phase increase the concentration and the mobility of the points defects responsible for the ionic conductivity.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…), and most of them are known to have an inhibitive action. Studies [5][6] have incited us to take advantage of the program of our laboratory to study natural extracts of essential oil as corrosion inhibitors. We have found that thyme [7][8], artemisia [8], castor-oil plant [9], spearmint [10] and verbena [11], etc., have got the power to be very effective corrosion inhibitors in acidic media.…”
Section: Introductionmentioning
confidence: 99%
“…LiI, AgI, AgCl, CdI 2 , TlI, CsHSO 4 , CsH 2 PO 4 and oxide insulators like SiO 2 , Al 2 O 3 , ZrO 2 , Fe 2 O 3 , MgO, TiO 2 etc. [7][8][9][10][11][12][13][14][15][16][17][18][19]. This method is recognized as an easier and more efficient because of not only the enhanced room temperature ionic conductivity, but also it boosts up the thermal and mechanical stability of the material.…”
Section: Introductionmentioning
confidence: 99%